2017
DOI: 10.1093/nar/gkx485
|View full text |Cite
|
Sign up to set email alerts
|

Universal attenuators and their interactions with feedback loops in gene regulatory networks

Abstract: Using a combination of mathematical modelling, statistical simulation and large-scale data analysis we study the properties of linear regulatory chains (LRCs) within gene regulatory networks (GRNs). Our modelling indicates that downstream genes embedded within LRCs are highly insulated from the variation in expression of upstream genes, and thus LRCs act as attenuators. This observation implies a progressively weaker functionality of LRCs as their length increases. When analyzing the preponderance of LRCs in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…The behavior (phenotype) of SSCs is controlled by coordinated activation and/or inhibition of thousands of genes. This coordination is achieved via a complex network of gene regulation that enables a cell to express the appropriate set of genes for a particular environment and/or phenotype [18]. The genome just needs to have enough instructions to recreate the required microenvironment so that the behavior can be sufficiently replicated within the required space to serve the required function.…”
Section: Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior (phenotype) of SSCs is controlled by coordinated activation and/or inhibition of thousands of genes. This coordination is achieved via a complex network of gene regulation that enables a cell to express the appropriate set of genes for a particular environment and/or phenotype [18]. The genome just needs to have enough instructions to recreate the required microenvironment so that the behavior can be sufficiently replicated within the required space to serve the required function.…”
Section: Homeostasismentioning
confidence: 99%
“…Liu et al demonstrated that, potential chaotic motifs are seen in the expression of certain genes in the cancer cell line and they conclude that more complex and somewhat more disorganized chaotic motifs can be found in cancer [18]. Ghosh et al considered a mathematic model, describing the interactions of cancer cells with their microenvironment and they demonstrated chaotic behavior of cancer cell [39].…”
Section: Evidence Supporting the Chaotic Adaptation Theorymentioning
confidence: 99%